Jødedommen som et hellenistisk fænomen - Otzen, Benedikt (Religionsvidenskabeligt Tidsskrift, 1990)
With the somewhat provocative title the theme is given: the relations between Hellenistic culture and Judaism. The Hellenistic impact upon Judaism is not restricted to the Diaspora (e.g. Egypt); also in Palestina Hellenism had a strong influence canalized through the many Hellenistic poleis, free cities. This fact is demonstrated with examples from the Book of Sira and from apocalyptics.